WRITING DESCRIPTIVE TEXT BY USING TWO-STAY TWO-STRAY TECHNIQUE: STUDENTS’ RESPONSE - Manap Abdul Rohman; Rissa San Rizqiya (PROJECT (Professional Journal of English Education), 2021)
The objective of this research was to investigate the students' responses in learning writing descriptive text through the two-stay two-stray technique. This research used a qualitative method and the design was descriptive qualitative. The respondents of the research were 23 seventh grade students of Junior High School in Cikadu. The data were obtained from questionnaires and interviews. The results of the research revealed that writing descriptive text using the two-stay two-stray technique can motivate students to join learning activities,  can reduce the time to understand the material, and they braver to express their idea. Keywords:  Two-Stay Two-Stray, Writing, Students’ Response